Regional Assessment of the Hydropower Potential of Rivers in West Africa. (November 2016) - Kling, Harald; Stanzel, Philipp; Fuchs, Martin
Abstract: In this study the theoretical hydropower potential of all rivers in West Africa was assessed. The study domain covers 5 Mio km 2 . For more than 500, 000 river reaches the theoretical hydropower potential was computed from channel slope and mean annual discharge simulated by a water balance model. The model was calibrated with observed discharge at 410 gauges, using precipitation and potential evapotranspiration data as inputs. Possible changes in future discharge were assessed by driving the water balance model with climate projections of 15 Regional Climate Models for two emission scenarios of the CORDEX-Africa ensemble.